THE EFFECT OF ISLAMIC BANKING FINANCING AND MACROECONOMIC VARIABLES ON ECONOMIC GROWTH IN INDONESIA, 2010-2020 - Riky Soleman (IQTISHADUNA, 2022)
Economic development in a country or region is essentially aimed at improving the welfare of its inhabitants. In this study using panel data analysis method in the form of a cross-section of 34 provinces in Indonesia with a time-series from 2010-2020. Followed by using quantitative analysis methods with the Eviews 10 analysis tool. The test results of the specification model state that FEM (Fixed Effect Model) is the best choice model to use. seen from all independent variables, only PMDN variable has a positive influence on economic growth. However, for the variables of Islamic Banking Financing, PMA Inflation and LFPR have a negative direction on Indonesia's economic growth. Thus, in the context of increasing economic growth, it can be ensured that the presence of several indicators such as a quality workforce and more productive investment coupled with more attention to the socialization of Islamic banking to the public means that economic growth in Indonesia is increasing and continues to increase.